Online Assessment of English Competence and Its Washback: Teachers’ and Students’ Voices - Mariam, Siti; Fadlilah, Sayyidatul; Kepirianto, Catur (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
Online assessments present several challenges for teachers, particularly in EFL (English as a Foreign Language) contexts. These difficulties fall into four categories: contextual, psychological, pedagogical, and technical. This study aims to explain teachers’ and students’ voices on implementing online assessment of English competence and its washback. It employed a qualitative method and a narrative inquiry research design. Data collection techniques used semi-structured interviews and open-ended questions. Thematic analysis was used as a data analysis technique. The participants were two English teachers and five students of an Islamic secondary school in Semarang city. The results show that the biggest challenge when conducting online English assessment reflects a range of technological, emotional, and instructional challenges, namely poor internet connection, device sharing or lack of equipment, speaking anxiety, unclear instructions, difficulty with listening tests, time pressure, lack of feedback, and technical platform confusion.